2016
DOI: 10.4238/gmr.15017814
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 4 diversity and correlation analysis with coat color in goat

Abstract: ABSTRACT. Desmoglein 4 (DSG4) has an important role in the development of wool traits in domestic animals. The full-length DSG4 gene, which contains 3918 bp, a complete open-reading-frame, and encodes a 1040-amino acid protein, was amplified from Liaoning cashmere goat. The sequence was compared with that of DSG4 from other animals and the results show that the DSG4 coding region is consistent with interspecies conservation. Thirteen single-nucleotide polymorphisms (SNPs) were identified in a highly variable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the DSG1 gene is involved in the communication of hair follicle cell and morphogenesis of hair follicle ( Hanakawa et al, 2004 ; Dong et al, 2013 ). The DSG4 gene affects wool traits and is responsible for coat color in Cashmere goats ( E et al, 2016 ). Furthermore, the DSG3 gene may have linked with additional fiber growth in the cashmere goats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the DSG1 gene is involved in the communication of hair follicle cell and morphogenesis of hair follicle ( Hanakawa et al, 2004 ; Dong et al, 2013 ). The DSG4 gene affects wool traits and is responsible for coat color in Cashmere goats ( E et al, 2016 ). Furthermore, the DSG3 gene may have linked with additional fiber growth in the cashmere goats.…”
Section: Discussionmentioning
confidence: 99%
“… Zhou et al., 2016 2 DSG4 106052985-106078954 Haplotypes related with the color of the goat coat. E et al., 2016 2 CABLES1 1 102881201-102953764 An adapter protein that links cyclin-dependent kinase with nonreceptor tyrosine kinases and regulates the activity of Cdks by enhancing their Y15 phosphorylation. Huang et al., 2017 2 GATA6 102636810-102654409 Promotes hair follicle progenitor cell renewal.…”
Section: Resultsmentioning
confidence: 99%
“…The core haplotypes constructed by using the 3 most significant SNPs (rs14228181, rs14227093, and rs14230934) were ranging from 102.3 Mb to 106.4 Mb where many candidate genes were located. Previous studies demonstrated that DSG4 was related with the goat white and black color ( E et al., 2016 ), and GATA6 promotes hair follicle progenitor cell renewal ( Wang et al., 2017 ). Besides, the dietary intake of tyrosine could influence the color expression of the hair coat of adult dogs ( Watson et al., 2018 ), and the YES1 as a candidate of interested is a member of the Src family tyrosine kinases.…”
Section: Discussionmentioning
confidence: 99%